Legal issues in counselling & psychotherapy - Jenkins, Peter, 1950- (Ethics in practice., 2002)
This text exmamines the rapidly growing range of situations in which therapists find themselves in contact with the law - in their everyday practice, in specialist work or when facing a legal case against them.